2013
DOI: 10.5194/npg-20-669-2013
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional ensemble-variational data assimilation for global deterministic weather prediction

Abstract: Abstract. The goal of this study is to evaluate a version of the ensemble-variational data assimilation approach (EnVar) for possible replacement of 4D-Var at Environment Canada for global deterministic weather prediction. This implementation of EnVar relies on 4-D ensemble covariances, obtained from an ensemble Kalman filter, that are combined in a vertically dependent weighted average with simple static covariances. Verification results are presented from a set of data assimilation experiments over two separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 34 publications
4
97
0
Order By: Relevance
“…The analyses were obtained from ECCC archives (Buehner et al, 2013Caron et al, 2015), in order to prevent chaotic drift of the model meteorology from observations. Consequently, our simulation setup comprises simulations on the North American domain in 30 h cycles starting at 12:00 UTC, and the oil sands domain in 24 h cycles starting at 18:00 UTC (the 6 h lag being required to allow meteorological spinup of the lower resolution model).…”
Section: Model Setup For Three Scenariosmentioning
confidence: 99%
“…The analyses were obtained from ECCC archives (Buehner et al, 2013Caron et al, 2015), in order to prevent chaotic drift of the model meteorology from observations. Consequently, our simulation setup comprises simulations on the North American domain in 30 h cycles starting at 12:00 UTC, and the oil sands domain in 24 h cycles starting at 18:00 UTC (the 6 h lag being required to allow meteorological spinup of the lower resolution model).…”
Section: Model Setup For Three Scenariosmentioning
confidence: 99%
“…In 4DEnVar (e.g. Buehner et al, 2013), a temporal localisation function could be introduced that was also dependent on the horizontal scale such that smallscale errors could be forced to decorrelate more rapidly through time than large-scale errors.…”
Section: Discussionmentioning
confidence: 99%
“…Houtekamer et al, 2014) and the more recent variational-ensemble (EnVar; e.g. Buehner et al, 2013) approaches. The computational cost of producing an ensemble of forecasts large enough to estimate sufficiently accurate and high-rank covariances is prohibitive.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the result of 4D-EnVAR is closer to the true value than that of 4D-VAR, because the background covariance matrix includes the information of ensemble forecasts as well as the climatology (e.g., Buehner 2005;Liu et al 2008;Buehner et al 2013). However, it is difficult to make clean comparisons between 4D-EnVAR and EnKF because generic variational data assimilation systems and EnKF systems differ in many respects of solution algorithm, which are optimized for each system to improve efficiency of the calculation, dynamical balance of the analysis, and so on (Buehner et al 2010).…”
Section: Introductionmentioning
confidence: 99%